Production of synthesis gas obtained via alkaline water electrolysis and added biomass - Gomes, João (2022)
This paper presents the results of the research currently being carried out at ISEL with the objective of developing new electrochemistry-based processes to obtain renewable synthetic fuels from alkaline water electrolysis using a carbon source. In the developed process, the gas mixture obtained from alkaline water electrolysis and a carbon source is not separated into their components but rather is introduced into a catalyzed reactor, in order to achieve conversion to synthetic 2nd generation biofuels, such as biomethane, biomethanol, bio-dimethyl ether, etc. Tests have been previously executed in a pilot electrolyzer and reactor of 1 kW, and are now being scaled up to a pilot electrolyzer and reactor of 5 kW, producing 250 l/h CH4, as an intermediate step to a pilot of 100 kW.